2003
DOI: 10.1081/ada-120018847
|View full text |Cite
|
Sign up to set email alerts
|

Predictors Of Drinking Outcomes Among Alcoholics

Abstract: Predicting outcomes for individual patients entering substance abuse treatment has long been a clinical goal in the addictions field. Intake data from the Addiction Severity Index and other standardized scales were collected on 248 alcohol dependent/abusing patients entering an urban hospital treatment program. The outcome measure was frequency of drinking days in the past 30 days. Baseline data were used to identify predictors of posttreatment drinking frequency at two follow-up interviews (3 and 12 months po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
23
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 19 publications
2
23
0
Order By: Relevance
“…In addiction treatment settings, where the use of social controls and coercive strategies is common, preliminary research has highlighted the relevance of self-determined motivation for positive treatment processes and outcomes (Ryan et al, 1995;Staines et al, 2003;Wild et al, 2006;Zeldman et al, 2004). This prior research used different measures of selfdetermined motivation with varying levels of validation in addiction treatment contexts.…”
Section: Discussionmentioning
confidence: 99%
“…In addiction treatment settings, where the use of social controls and coercive strategies is common, preliminary research has highlighted the relevance of self-determined motivation for positive treatment processes and outcomes (Ryan et al, 1995;Staines et al, 2003;Wild et al, 2006;Zeldman et al, 2004). This prior research used different measures of selfdetermined motivation with varying levels of validation in addiction treatment contexts.…”
Section: Discussionmentioning
confidence: 99%
“…They also emphasized the idea that combined treatments can add up and the association can be more effective. Another study concluded that the index of 12-step participation was predictive of the outcome (Staines et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…On the one hand, a number of studies have examined 12-step meeting attendance as an integral part of 12-step involvement (e.g., Humphreys et al, 1998;Mankowski, Humphreys, & Moos, 2001;McKellar et al, 2003;Moos & Moos, 2007;Morgenstern, Labouvie, McCrady, Kahler, & Frey, 1997;Staines et al, 2003;Tonigan et al, 1998;Zenmore, Kaskutas, & Ammon, 2004). On the other hand, fewer investigations have examined involvement apart from 12-step meeting attendance.…”
mentioning
confidence: 99%